Stigmatization and resilience in inflammatory bowel disease patients at one-year follow-up - Lenti, Marco Vincenzo; Broglio, Giacomo; Mengoli, Caterina; Cococcia, Sara; Borrelli de Andreis, Federica; Vernero, Marta; Pitotti, Lavinia; Padovini, Lucia; Secco, Matteo; Delliponti, Mariangela; Corazza, Gino Roberto; Klersy, Catherine; et al. (Frontiers in Gastroenterology, 2022)
Introduction Inflammatory bowel disease (IBD), namely ulcerative colitis and Crohn’s disease, is a chronic relapsing immune-mediated condition that may cause an impairment of social functions due to stigmatisation. Resilience instead is associated with an improvement in coping with adversities and thus may counteract the detrimental effects of stigmatisation. We herein sought to determine the fluctuation of stigmatisation and resilience in a cohort of patients with IBD at 1-year follow-up. Methods This is a prospective, monocentric study conducted in a tertiary referral centre. All patients with IBD were assessed at enrolment and at oneyear follow-up. Several clinical and demographic variables were collected. Stigmatisation was assessed through a validated Italian version of the Perceived Stigma Scale for IBD (PSS-IBD), while resilience was assessed through the 25-item Connor Davidson Resilience Scale (CD-RISC25). Also, self-efficacy (SEF) and self-esteem (SES) scales were assessed. Results In this study, 105 patients were included (46 Crohn’s disease, 59 ulcerative colitis; overall mean age 47 years ±11, M:F ratio 1:1.2). None of the 4 scales showed a statistically significant variation at one year compared to baseline (median CD-RISC25 64 at baseline vs 61 at follow-up; SEF 31 vs 30; SES 32.5 vs 32; PSS-IBD 0.45 vs 0.45). A statistically significant and inverse correlation was found between CD-RISC25 and PSS-IBD (rho -0.222, p=0.01), SEF and PSS-IBD (rho -0.219, p= 0.01), SES and PSS-IBD (-0.316, p=0.003). CD-RISC25 was found to be positively associated with inactive IBD (p=0.05). Discussion In this prospective study we have shown for the first time that stigmatisation, resilience, SEF and SEM did not change over a one-year time span, suggesting that, based on the information gathered, these characteristics may be independent from IBD severity or IBD flares. Furthermore, we found an inverse correlation of stigma with resilience, SEF and SES, suggesting an important role that these variables may have on preventing stigmatisation.